Waves-sea ice interactions in polar seas - Boutin, Guillaume (HAL CCSD, 2018)
Sea ice, which covers most of the ocean near the poles, is a key component of the climate system. Global warming is driving its massive melting, especially in the Arctic. Where sea ice cover decreases, fetch increases leading to more energetic sea states. This means potentially enhanced wavesice interactions effects in the future. The quick evolution of sea ice extent and volume combined with the intensification of human activities in polar regions urge us to improve our understanding of waves-ice interactions.Sea ice attenuates waves. They can however propagate through it and break it far into the ice cover. Attenuation depends on ice properties such as floe size, thickness, etc. Once broken, resulting floes are more likely to drift and melt. In addition, wave attenuation yields a force which pushes the floes in the direction of wave propagation.A simplified representation of sea ice, including a floe size distribution, has been incorporated in a wave model.It allows us to show the important contribution of dissipative mechanisms in the wave attenuation, especially those induced by the bending of the ice plates. After validation, the modified wave model is coupled to an ice model. The floe size distribution is exchanged in the coupled framework and used in ice lateral melt computation. The force exerted by the waves on the ice floes is sent from the wave model and is shown to compact sea ice in summer. This reduces the melting and significantly increases the temperature and salinity in the surface ocean close to the ice edge. La banquise, qui couvre de larges étendues de l’océan près des pôles, est une composante majeure du climat. Le réchauffement de la planète entraîne sa fonte massive, en particulier en Arctique.Là où l’extension de la banquise diminue, l’augmentation du fetch est associée à une élévation de la hauteur des vagues, laissant penser que les effets liés aux interactions vagues-glace pourraient s’accroître dans le futur. L’évolution rapide de la banquise associée à l’intensification des ...